Manajemen Pendidikan Bermuatan Antropologi, Agama dan Sosial - Ivan Riyadi (Cendekia: Kependidikan dan Kemasyarakatan, 2019)
Abstract: This article discusses management of education in collaboration with anthropology, religion and social education which adopts diversity. Religion as a factual behaviour can only be captured through an analysis of a system of religious behaviour. It involves some components. In understanding Islamic education, religiousness is a necessity for each follower in order not to be trapped in the view of the practical uniformity of diversity. Each religious unit is related to differences in nature and the conditions of each component of the religious system. As an example, understanding can realize that religious teaching remains universal, through culture, and social. However, the praxis of teaching is a singularity. Therefore, a diverse number of events are carried out as a consequence of religious belief. The role of education management is very important, especially for educational institutions which adapt the students’ cultural and social conditions needs. ملخص: يناقش هذا المقال في إدارة التعليم مع الأنثروبولوجيا والدين والتعليم الاجتماعي كوسيلة لاعتماد التنوع. ولا يمكن التقاط الدين كسلوك واقعي لأي دين إلا من خلال تحليل نظام للسلوك الديني الذي يشمل عددا من المكونات. في تطبيق التربية الإسلامية، كان الفهم للدين لازم لعدم التعلق في وجهة نظر التوحيد العملي من قبل كل متابع. كل وحدة دينية هي التفرد المرتبطة بالاختلافات في طبيعة وحالة كل عنصر من عناصر النظام الديني. هذا الفهم يمكن أن ندرك أن التعاليم الدينية لا تزال عالمية من خلال الثقافة والاجتماعية، في حين أن ممارسة التدريس هي وحدة فريدة، وبالتالي يتم تنفيذ عدد من وحدات النشاط المتنوعة نتيجة للمعتقدات الدينية. ولذلك دور إدارة التربية مهم جداً وخاصة المؤسسات التربوية التي تتكيف مع الظروف الثقافية والاجتماعية لاحتياجات الطلا ب.